2018
DOI: 10.3390/info9060135
|View full text |Cite
|
Sign up to set email alerts
|

Going beyond the “T” in “CTC”: Social Practices as Care in Community Technology Centers

Abstract: Community technology center (CTC) is a term usually associated with facilities that provide free or affordable computer and internet access, and sometimes training, to people in underserved communities. Despite the large number of studies done on CTCs, the literature has focused primarily on the use of ICTs as the main, if not the only, activity in these centers. When it comes to addressing social concerns, the literature has often seen them as an outcome of ICT use. It does not highlight CTCs as an inherent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 38 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…To bridge this digital divide, Community Technology Centres (CTCs), which are public-shared access to ICT resources with computers, Wi-Fi and, in some cases, mobile devices have been deployed in low-income contexts (Nemer, 2018b). Studies assessing CTCs in Brazil and Kenya indicated these facilities provide positive benefits that enable users to access information on education, health, current affairs (Wamuyu, 2017) and provide a social space to address individual and community needs (Nemer, 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…To bridge this digital divide, Community Technology Centres (CTCs), which are public-shared access to ICT resources with computers, Wi-Fi and, in some cases, mobile devices have been deployed in low-income contexts (Nemer, 2018b). Studies assessing CTCs in Brazil and Kenya indicated these facilities provide positive benefits that enable users to access information on education, health, current affairs (Wamuyu, 2017) and provide a social space to address individual and community needs (Nemer, 2018a).…”
Section: Introductionmentioning
confidence: 99%